2009
DOI: 10.1093/europace/eup312
|View full text |Cite
|
Sign up to set email alerts
|

Do gender differences exist in pacemaker implantation?--results of an obligatory external quality control program

Abstract: This large-scale real-life patient cohort of primary stationary pacemaker implantation showed that gender has an impact onto pacemaker implantation, with less favourable outcomes for women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
72
4
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 26 publications
14
72
4
2
Order By: Relevance
“…In general, women are more likely to have SSS, atrioventricular nodal reentrant tachycardia, and long QT syndrome. On the other hand, men are more likely to have atrioventricular block, atrioventricular reentrant tachycardia, idiopathic ventricular fibrillation, and BS 15, 16. A family history of SD or a Brugada‐type ECG is important for the management of BS.…”
Section: Discussionmentioning
confidence: 99%
“…In general, women are more likely to have SSS, atrioventricular nodal reentrant tachycardia, and long QT syndrome. On the other hand, men are more likely to have atrioventricular block, atrioventricular reentrant tachycardia, idiopathic ventricular fibrillation, and BS 15, 16. A family history of SD or a Brugada‐type ECG is important for the management of BS.…”
Section: Discussionmentioning
confidence: 99%
“…12 Additionally, research suggests that there may be differences between the sexes at pacemaker implantation, with less favourable outcomes for women in terms of complications. 13 Patients with SSS are at risk of developing a complete AV block, with considerable variation in the estimates of risk of AV block (from < 1% up to 4.5% per year). 4,14 A patient with SSS who develops AV block will require ventricular pacing (VP) and, consequently, an upgrade to a dual-chamber pacemaker if they already have a single-chamber atrial pacemaker.…”
Section: Description Of Health Problemmentioning
confidence: 99%
“…In an analysis on 36,312 elderly Medicare beneficiaries undergoing pacemaker implantation, Lamas et al showed that male gender was an independent predictor of a dual-chamber pacemaker implantation, 33 thus supporting a sex-bias in pacemaker implantation procedures. 34,35 With regard to complications, females experience more adverse events from pacemaker implantation. 35 Nowak et al recently reported that women had increased rates of procedure-related complications than men, with higher incidence of pneumothorax (odds ratio (OR) 2.12, 95 % confidence interval (CI) 1.39-3.24), especially when analysing the subclavian vein access group (OR 4.02, 95 % CI 1.91-8.45), and a higher incidence of pocket haematoma (OR 1.49, 95 % CI 1.05-2.11).…”
Section: Permanent Pacemakersmentioning
confidence: 99%
“…35 Nowak et al recently reported that women had increased rates of procedure-related complications than men, with higher incidence of pneumothorax (odds ratio (OR) 2.12, 95 % confidence interval (CI) 1.39-3.24), especially when analysing the subclavian vein access group (OR 4.02, 95 % CI 1.91-8.45), and a higher incidence of pocket haematoma (OR 1.49, 95 % CI 1.05-2.11). 35 In addition to women's older age and co-morbidities, smaller body size of females and a more challenging implantation procedure due to thinner right ventricular wall, smaller blood vessel diameter and a higher prevalence of anatomical variations in venoarterial relationships may explain such findings. 21,[35][36][37][38] On the other side, female gender seems associated with a better outcome after pacemaker placement, with males experiencing poorer survival following pacemaker implantation.…”
Section: Permanent Pacemakersmentioning
confidence: 99%
See 1 more Smart Citation